Evaluation of the Quality and Quantity Dental Wastes in Dental Centers of Mashhad City, 2017 - Ali Pakfetrat; Ali Sajjadi; aliakbar dehghan (Mashhad University of Medical Sciences, 2018)
ABSTRACT Background & Objectives: Today, one of the most important environmental issues is dental solid wastes due to its high contents of toxic, pathogen and hazardous agents. The aim of this study was to quantity and quality analyses of dental solid waste in dental centers of Mashhad. Materials & Methods:In this descriptive study 40 Dental centers were studied. From each Dental centers, three samples were analyzed at the successive working days (Sunday, Monday and Tuesday). The samples were manually sorted into 64 different components and measured by digital scale. Then, measured components were classified on the basis of characteristic and hazardous potential as well as material type. Data analyzed by using descriptive statistics, SPSS 16 software. Results:According to the results, total waste produced in dental centers in Mashhad was 224.137 kg/day. Per capita and the average generation rate of each dentistry center were 106.32 g/day-patient and 5603 g/day, respectively. Potential infectious, domestic-type, chemical & pharmaceutical, and toxic wastes consisted of 41.24, 44.17, 9.89, and 4.7% of the waste generated, respectively. Conclusion: The per capita waste generation in dental clinics in Mashhad is high and the highest share are related to infectious and domestic-type wastes.